THE METAPHORICAL DIMENSION OF LGBTQ INFORMATION: Challenges for its subject representation - Chaves Guimaraes, Jose Augusto [UNESP]; Nascimento, Francisco Arrais [UNESP]; Pinho, Fabio Assis (Univ Federal Campina Grande, 2017)
Having language as a practice of signification, permeating every system of representation that subsidizes forms of resistance and escape lines, one has the possibility of visualizing the processes by which the identities of the subjects are constructed, leading us to think The performativity. It is proposed to enter the sphere of the gender discussions, under the gore of the discourse, being situated theoretically-methodologically in a discursive-deconstructionist perspective, resorting to Foucaultian-based poststructuralist studies, in addition to the relation with queer theorizations, in the form of documentary research of an exploratory nature based on 25 minutes published between 2006 and 2013 by two Non-Governmental Organizations -NGOs in the Cariri Cearense region of Northeast Brazil. The objective was to understand the contribution of the Knowledge Organization -KO in the representation of the discursive practices of the LGBTQ universe. Guiding the research under the contributions of Albrechtsen and Hjorland (1995), Hjorland (1997, 1999, 2002), Tennis (2012) and Guimaraes (2008) in the scope of Information Science. In addition to the contributions of the work of Foucault and studies of representation and linguistics. Finally, the results revealed that the themes of the LGBTQ discursive community constitute a complex and highly metaphorical universe, much owed to the marginal conditions that refer to the history of this area, with strong prejudices about sexual practices. This situation demands a greater ethical concern with the indexation and classification systems, so that they can represent all the thematic wealth of the domain, from the documents of the subjects and the communities able to lead the understanding and search of identities that surround them.
Keywords: Knowledge Organization; Representation; LGBTQ